Spectral Characteristics of Nonlinear-Dispersive Similariton Generated in Single-Mode Fiber without Gain - H. Toneyan; K. Manoukyan; M. Sukiasyan; A. Kutuzyan; L. Mouradian
We report the studies of the spectral features of nonlinear-dispersive similariton generated in a passive single-mode fiber (without gain) with the aim of development-processing of similaritonic technique for pulse duration measurement in femtosecond time scale. Particularly, the dependence of the similariton spectral bandwidth from the input pulse energy and duration is studied in details both numerically and experimentally, to determine the input pulse duration alternatively to the autocorrelation technique.
Keywords: Physics; Optics